Ripley's believe it or not! 2011 - Ripley, Robert L. (Ripley Publishing London, 2010)
Gasp at extraordinary true tales about vampires, the Ripley's waxwork gallery, and the feats of sword swallowers past and present.Illustrated throughout with colour photographs and two pullouts featuring astounding lifesize images, this fascinating book is a must-have for anyone who loves jaw-dropping images and unbelievable facts.